2020
DOI: 10.1155/2020/6075902
|View full text |Cite
|
Sign up to set email alerts
|

circHIPK3 Acts as Competing Endogenous RNA and Promotes Non-Small-Cell Lung Cancer Progression through the miR-107/BDNF Signaling Pathway

Abstract: Circular RNAs (circRNAs) act as a crucial part in many human diseases, particularly in cancers. circRNA HIPK3 (circHIPK3) is a special circRNA that may participate in the oncogenesis of non-small-cell lung cancer (NSCLC), even though its latent regulatory mechanism is not very clear. Here, we studied the roles of circHIPK3 in NSCLC. qRT-PCR assay was applied to study the expression of circHIPK3 in NSCLC. The influence of circHIPK3 on NSCLC was estimated by silencing circHIPK3 and miR-107 mock transfection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…For example, circHIPK3 was upregulated in CC and accelerated multiplication of CC cells via the miR-485-3p/FGF2 axis (10). Meanwhile, circHIPK3 enhanced the progression of NSCLC via the miR-107/BDNF signaling pathway (11). CircRNA HIPK3 upregulated CCND2 expression in OSCC via miR-124, thus promoting cell proliferation and invasion (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, circHIPK3 was upregulated in CC and accelerated multiplication of CC cells via the miR-485-3p/FGF2 axis (10). Meanwhile, circHIPK3 enhanced the progression of NSCLC via the miR-107/BDNF signaling pathway (11). CircRNA HIPK3 upregulated CCND2 expression in OSCC via miR-124, thus promoting cell proliferation and invasion (12).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that CircHIPK3 is related to tumor progression, indicating that CircHIPK3 can regulate tumor progression. An increasing number of studies have demonstrated the involvement of circHIPK3 in the progression of cervical cancer (CC), nonsmall-cell lung cancer (NSCLC), and OSCC as an oncogene (10)(11)(12). However, the mechanism of circHIPK3 in OSCC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Further study ( 63 ) demonstrated that circHIPK3 induced cell proliferation and inhibited apoptosis in NSCLC by sponging miR-149, indirectly increasing FOXM1 expression. Similarly, Hong et al ( 64 ) confirmed that circHIPK3 promoted NSCLC progression via a circHIPK3/miR-107/brain-derived neurotrophic factor (BDNF) axis, highlighting potential markers for NSCLC screening. A study by Chen et al ( 65 ) demonstrated that circHIPK3 functioned as an oncogene, and loss of circHIPK3 significantly impaired cell proliferation, migration and invasion, and induced protective autophagy via a miR-124-3p/STAT3/protein kinase AMP-activated catalytic subunit a2/AMPKa axis in serine/threonine kinase 11-mutant LC cell lines (A549 and H838; Fig.…”
Section: Circhipk3 and Human Diseasesmentioning
confidence: 92%
“… 94 circHIPK3 Up miR-107 H1299, A549, and BEAS-2B NSCLC cell lines circHIPK3 promotes the migration and proliferation of NSCLC cells by sponging miR-107 to upregulate BDNF expression Hong et al. 95 circ_0074027 up miR-335-5p 60 NSCLC tissue samples; H358, H1299, H1581, and A549 NSCLC cell lines circ_0074027 promotes cell viability, cell-cycle process, and colony formation and inhibits apoptosis in NSCLC cells by sponging miR-335-5p to increase GUL4B expression Yu et al. 96 circSEC31A up miR-376a 44 NSCLC tissue samples; A549 and H1299 NSCLC cell lines circSEC31A promotes NSCLC cell migration, invasion, and glycolysis and inhibits apoptosis by sponging miR-376a to increase SEC31A expression Cheng et al.…”
Section: Overview Of Circrnasmentioning
confidence: 99%